The Influence of Peers on Student Motivation - Dzirlyfira Nurul Azzahfa; Mukhammad Bakhruddin; Hayumuti (Program Studi Pendidikan Agama Islam Fakultas Ilmu Tarbiyah Dan Keguruan UIN Raden Fatah, 2024)
Teaching and learning activities, which are the learning process, are the main thing, which means that the success or failure of achieving learning objectives depends on how the teaching and learning process is designed and carried out. The current education system is still concerned with academic aspects alone. Whereas education should develop the potential of students comprehensively. Intellectual, emotional and spiritual intelligence need to be developed together. The research aims to find out the relationship between peer association and student learning motivation. The research design used in this study uses a quantitative research approach with a correlational descriptive method. The results showed that the variable X1 (Peers) had a beta coefficient value of 0.783 with a significance value of 0.000. based on these results it can be seen that peers (X1) have a positive and significant effect on student learning motivation at SMA Muhammadiyah 1 Babat indicated by a sig value <0.05 (0.000).